INTERPRETATION OF ALTERATION MINERALS AROUND THE OMA-HARUKU HOT SPRINGS, CENTRAL OF MOLUCCAS - Helda Andayany; Josephus Ronny Kelibulin (SCIENCE NATURE, 2019)
Petrographic analysis to rock samples located at Oma-Haruku hot springs was dominated by mudstone. Another alteration mineral types of the rocks in this area are quartz, aragonite/calcite and feldspar minerals. Petrographic analysis was supported by the XRD method. The method indicated that the alteration minerals content was generally dominated by the presence of aragonite/calcite with particle size of 0.05 - 2 mm, the abundance of 55% and the spread evenly. Based on such presence of aragonite/calcite, one can interpret that the origin rock was carbonate. Alteration minerals which were generally dominated by mudstone indicate that the type of hot spring area in Oma-Haruku is a type of high-temperature reservoir, namely > 175 oC. Therefore, the area is potentially as geothermal field in Central of Moluccas.